SAT0372 Clinical and serological associations of autoantibodies to BICD2 as a novel marker for systemic sclerosis. (15th June 2017) - Mahler, M; Bentow, C; Milo, J; Hudson, M; Zucht, H-D; Budde, P; Wirtz, D; Schulte-Pelkum, J; Choi, M; Fritzler, M
Abstract : Background: Anti-nuclear antibodies (ANA), which are present in approximately 90% of systemic sclerosis (SSc) patient's sera, play an important role in establishing the diagnosis and predicting prognosis of SSc. Recently, a novel autoantibody has been described in SSc patients targeting Cytoskeleton-Like Bicaudal D Protein Homolog 2 (BICD2). Objectives: The aim of this study was to assess the prevalence and titers of anti-BICD2 antibodies in SSc and controls and to study the clinical associations of this new antibody. Methods: A total of 502 samples from SSc patients enrolled in the Canadian Scleroderma Research Group (CSRG) cohort were included in this study. Clinical associations were assessed either as anti-BICD2 antibody positivity with and without other autoantibodies present using 451 SSc patients with complete dataset. Autoantibodies to several scleroderma-related autoantibodies were detected using commercial or research use only kits (Inova Diagnostics, San Diego, USA). P-values below 0.05 were considered significant. Results: The sensitivity and specificity of anti-BICD2 antibodies were determined as 22.1% and 99.0%, respectively. Receiver operating characteristic (ROC) analysis showed an area under the curve of 0.79 (95% CI 0.75–0.84). The likelihood (LR) and odds ratios (OR) were 17.7 (LR+), 0.8 (LR-) and 20.4 (OR). The prevalence of these autoantibodies was equally distributed between limited and diffuse form of SSc (22.8% and 24.0%). When SSc patients without the classification criteria markers anti-Scl-70, anti-Centromere and anti-RNA Pol III (n=184) were compared with controls, similar performance was obtained as seen in the entire cohort. Results are summarized in table 1 below. Several statistically relevant clinical associations were found for anti-BICD2 as summarized in table 2 below. Conclusions: Our data confirm the presence of anti-BICD2 antibodies in SSc patients that may help to differentiate SSc from other systemic autoimmune rheumatic diseases and to stratify SSc patients into more defined subforms of the disease. Disclosure of Interest: M. Mahler Employee of: Inova Diagnostics, C. Bentow Employee of: Inova Diagnostics, J. Milo Employee of: Inova Diagnostics, M. Hudson: None declared, H.-D. Zucht Employee of: Protagen, P. Budde Employee of: Protagen, D. Wirtz Employee of: Protagen, J. Schulte-Pelkum Employee of: Protagen, M. Choi: None declared, M. Fritzler: None declared